STRATEGI PENGEMBANGAN BISNIS DENGAN PENDEKATAN BUSINESS MODEL CANVAS DAN METODE SWOT-AHP PADA PERUSAHAAN STARTUP LINGKUNGAN : (Studi Kasus Di Solusibanjir.id) - Prama Shandyasta Mahindriya, (2021)
SolusiBanjir.id (SBID) is an environmental startup that focuses on education and providing solutions to manage floods and water conservation through wise water management and water absorption. SBID needs to find the right business development strategy because flood especially in DKI Jakarta are increasing, this can be seen from the number of affected RWs in DKI Jakarta area in 2019 - 2020 where the number of affected RWs has increased by 1219 RW. The purpose of this research is to design a business development strategy based on an analysis of the company's internal and external factors and then it is poured into a business model. The methods used in this study are IFE and EFE matrix, IE matrix, SWOT, AHP, and BMC. IE matrix shows that SBID is in cell V, namely hold and maintain. There are three alternative strategies based on the IE and SWOT matrix. In the AHP calculation, the main factor that plays a role in the business development strategy is marketing, the main actor is Board of Directors, and the main alternative strategy is collaborating with other organizations in the water sector. The chosen alternative strategy is then poured into the BMC in the Key Partnership and Key Activities block.